Laparoscopic umbilical herniorrhaphy: a novel technique of hernia neck closure and outcomes in the first 19 cases - Vetter, Cheyenne; Pillay, Yagan (Laparoscopic Surgery, 2018)
Background: Laparoscopicrepair of umbilical hernias are still in its infancy and we present a newapproach to an old problem. Methods: Laparoscopicrepair of umbilical hernias were performed on 19 patients in which the hernianeck was addressed by suturing it closed with a non-absorbable suture and thenapplying an underlay mesh. Data was obtained from operative reports and thesurgeon’s electronic medical records (EMRs). All surgeries were performed by asingle surgeon in a rural hospital in northern Saskatchewan. Results: The resultsshowed no hernia recurrences over a two year follow up.88 percent of patientswere male with BMIs in the range of 22.6–45.3. Six patients had more than 1hernia and the average operative time was 84.75 minutes. Conclusions: Laparoscopicumbilical herniorrhaphy with intra corporeal neck closure is a viable form ofhernia repair. None of the patients presented with umbilical wound infectionsdue to the lack of an incision at the umbilicus. There were also good cosmeticresults due to the reapproximation of the subcutaneous tissue resulting in theformation of a new umbilicus without the obvious scar and deformation oftenassociated with an open repair. A randomised trial is now required as well alonger follow up to determine the efficacy of this technique. The outcomes inthe first 19 patients show a novel technique for umbilical herniorrhaphy whichin the era of laparoscopic surgery we hope will add to the surgicalarmamentarium.